2017
DOI: 10.3350/cmh.2016.0041
|View full text |Cite
|
Sign up to set email alerts
|

A lexicon for hepatocellular carcinoma surveillance ultrasonography: benign versus malignant lesions

Abstract: Background/AimsTo suggest a lexicon for liver ultrasonography and to identify radiologic features indicative of benign or malignant lesions on surveillance ultrasonography.MethodsThis retrospective study included 188 nodules (benign, 101; malignant, 87) from 175 at-risk patients identified during surveillance ultrasonography for hepatocellular carcinoma. We created a lexicon for liver ultrasonography by reviewing relevant literature regarding the ultrasonographic features of hepatic lesions. Using this lexicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 14 publications
0
6
2
Order By: Relevance
“…[14][15][16] Nonetheless, nodule echogenicity does not distinguish HCC and benign nodules. 17 While uncommon in our study, a hypoechoic rim was found more frequently with HCC (20%) than benign (0.2%) nodules. In 2008, Forner et al reported that a halo or hypoechoic rim is found in 76.47% of HCCs, whereas in only 11.54% in non-HCC nodules.…”
Section: Subgroup Analysis Of Small Liver Lesionscontrasting
confidence: 45%
See 3 more Smart Citations
“…[14][15][16] Nonetheless, nodule echogenicity does not distinguish HCC and benign nodules. 17 While uncommon in our study, a hypoechoic rim was found more frequently with HCC (20%) than benign (0.2%) nodules. In 2008, Forner et al reported that a halo or hypoechoic rim is found in 76.47% of HCCs, whereas in only 11.54% in non-HCC nodules.…”
Section: Subgroup Analysis Of Small Liver Lesionscontrasting
confidence: 45%
“…All US surveillance was performed by or under the supervision of board-certified radiologists. The US features assessed included nodule size, echogenicity, rim, and posterior acoustic enhancement (adopted from An et al 17 ).…”
Section: Ultrasonography and Ultrasound Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the results by directly comparing the sensitivity of the three methods suggest that CNB may be the most sensitive one (93.6%) for both primary liver cancer and metastatic cancers, and the TIC has comparable sensitivity in metastatic lesions (93.4%). In the clinical practice, prior to receiving liver biopsies, those patients usually undergo ultrasonographic and radiologic examinations, revealing certain degree of suspicion for malignancy [ 9 , 10 ]. The results of the current study, including the sensitivity of each method as well as the factors associated with the sensitivity, may help the clinical physicians select the appropriate techniques with satisfactory sensitivity and safety for patients with suspected hepatic malignancies on images.…”
Section: Discussionmentioning
confidence: 99%